2022
DOI: 10.3390/jpm12050683
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Class Classification of Breast Cancer Using 6B-Net with Deep Feature Fusion and Selection Method

Abstract: Breast cancer has now overtaken lung cancer as the world’s most commonly diagnosed cancer, with thousands of new cases per year. Early detection and classification of breast cancer are necessary to overcome the death rate. Recently, many deep learning-based studies have been proposed for automatic diagnosis and classification of this deadly disease, using histopathology images. This study proposed a novel solution for multi-class breast cancer classification from histopathology images using deep learning. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Umer et al 21 presented a DL method for multi-class BC classification using a 6B-Net deep CNN model enhanced with feature fusion and selection. Evaluated on BreaKHis with 7909 images across eight classes and another BC histopathology dataset of 3771 images in four classes, the approach achieved 94.20% accuracy for the four-class set in 226 s and 90.10% for the eight-class set in 147 s.…”
Section: Related Workmentioning
confidence: 99%
“…Umer et al 21 presented a DL method for multi-class BC classification using a 6B-Net deep CNN model enhanced with feature fusion and selection. Evaluated on BreaKHis with 7909 images across eight classes and another BC histopathology dataset of 3771 images in four classes, the approach achieved 94.20% accuracy for the four-class set in 226 s and 90.10% for the eight-class set in 147 s.…”
Section: Related Workmentioning
confidence: 99%
“…However, due to the complexity of early breast cancer and the dimming of mammography images, it is challenging for clinicians to diagnose cancer from these images. As a result, it is crucial to improve a doctor’s detection effectiveness using the CAD system of deep learning approaches [ 26 ].…”
Section: Related Workmentioning
confidence: 99%
“…Two pre-trained models resnet34 and resnet50 were utilized to transfer the learned feature for classification tasks with different training testing ratios of the dataset [34]. For more understanding of BC classification and segmentation interested readers are referred to the latest studies found in [35][36][37][38].…”
Section: Related Workmentioning
confidence: 99%